Comparison of diffusion-weighted MR imaging and 18F Fluorodeoxyglucose PET/CT in detection of residual or recurrent tumors and delineation of their local spread after (chemo) radiotherapy for head and neck squamous cell carcinoma. Issue 130 (September 2020) - Schroeder, Christophe; Lee, Jung-Hyun; Tetzner, Ulrich; Seidel, Stefan; Kim, Soung Yung
Abstract: Purpose: To compare the diagnostic accuracy of diffusion-weighted magnetic resonance imaging (DW-MRI) and fluorine 18 fluorodeoxyglucose positron emission tomography/computed tomography ( 18 F-FDG PET/CT) in detection of residual or recurrent tumors and their local extension in patients with head and neck squamous cell carcinoma after treatment with (chemo) radiotherapy (CRT). Method: Twenty-five patients (17 men, 8 women, median age 64 years, range 49–79) who underwent surgical salvage for residual or recurrent tumors after CRT were included. The histopathologic analysis after the surgical salvage served as the gold standard. Results: Both DW-MRI and 18 F-FDG PET/CT had a sensitivity of 92 % (23/25) in the detection of residual or recurrent tumors. MRI had a sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) for detecting perineural spread of 62 % (5/8), 88 % (15/17), 71 % (5/7) and 83 % (15/18), respectively; in comparison, PET/CT did not detect any cases of perineural spread. The sensitivity, specificity, PPV and NPV of MRI in detecting muscle infiltration was 75 % (9/12), 77 % (10/13), 75 % (9/12) and 77 % (10/13) respectively, while the values for 18 F-FDG PET/CT were 58 % (7/12), 69 % (9/13), 64 % (7/11) and 64 % (9/14). Conclusions: DW-MRI- and 18 F-FDG PET/CT-imaging have an identical detection rate of residual or recurrent tumors after (chemo) radiotherapy. MRI has a higher sensitivity in detecting local perineural spread, has a better accuracy in the detection of muscle infiltration and more accurately correlates the lesion size to the histopathologic specimen.